«¡Vio cómo el negro tiene derecho!» El debate etno-racial y político de las comunidades quilombolas en el sur del Brasil 1 - Rodríges, Vera (2006)
his article inserts itself in the point of view of anthropological outputs that approach to thematic of the emergency of political and ethnic contests, been at the center of by the Communities Quilombolas in Brazil, in relation with similar experiences in the Latin and Central America. For so much, it analyzes the trial that engenders the claim of right partner-cultural of the Quilombo of the Anastácia, a community located in the south of Brazil and that comes building a path of resistance and fight in that that the native speeches name as it seeks by their lost lands. In that social dynamics incorporate itself diverse social agents, such as Black Social Movement and Agents of the Public Power, whose acts contribute for the (re) making of ethnic and collective identities